2018
DOI: 10.1016/j.clim.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and dietary micronutrient deficiencies contribute to overexpression of epigenetically regulated genes by lupus T cells

Abstract: Patients with active lupus have altered T cells characterized by low DNA methyltransferase levels. We hypothesized that low DNA methyltransferase levels synergize with low methionine levels to cause greater overexpression of genes normally suppressed by DNA methylation. CD4+ T cells from lupus patients and controls were stimulated with PHA then cultured in custom media with normal or low methionine levels. Oxidative stress was induced by treating the normal CD4+ T cells with peroxynitrite prior to culture. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…A mechanistic rationale exists for evaluating these 4 dietary scores in relation to SLE onset. Oxidative stress and other environmental exposures, including diet, can contribute to lupus onset and flares through epigenetic mechanisms that modify CD4+ T cell gene expression (33). Although we did not demonstrate that high adherence to the AHEI‐2010 or aMed dietary scores reduces the risk of SLE, our results demonstrate a potential reduction in SLE risk with high nut/legume intake, which also includes soy products.…”
Section: Discussionmentioning
confidence: 99%
“…A mechanistic rationale exists for evaluating these 4 dietary scores in relation to SLE onset. Oxidative stress and other environmental exposures, including diet, can contribute to lupus onset and flares through epigenetic mechanisms that modify CD4+ T cell gene expression (33). Although we did not demonstrate that high adherence to the AHEI‐2010 or aMed dietary scores reduces the risk of SLE, our results demonstrate a potential reduction in SLE risk with high nut/legume intake, which also includes soy products.…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of evidence has shown that aberrant epigenetic modifications contribute to CD4 + T cell activation and the pathogenesis of SLE [4,[41][42][43]. The epigenetic regulator UHRF1 typically alters DNA methylation and histone modification to regulate gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, diet supplemented with vitamins (A, B6, C, D or E) resulted in improvement of flares and symptoms of SLE (10) . Ray et al (2018) hypothesised that expression of genes susceptible to DNA methylation in T cells from SLE patients may be more prevalent in low-micronutrient conditions than in healthy T cells. They cultured CD4 þ T cells from lupus patients PHA-stimulated in culture media with normal or low levels of B6 and B12 vitamins, methionine, folate and choline, and then measured expression of CD70, perforin and KIR (171) .…”
Section: Diet Epigenetic and Sle Linkagementioning
confidence: 99%
“…Ray et al (2018) hypothesised that expression of genes susceptible to DNA methylation in T cells from SLE patients may be more prevalent in low-micronutrient conditions than in healthy T cells. They cultured CD4 þ T cells from lupus patients PHA-stimulated in culture media with normal or low levels of B6 and B12 vitamins, methionine, folate and choline, and then measured expression of CD70, perforin and KIR (171) . It should be noted that KIR, perforin and CD70 genes are usually hypermethylated and overexpressed in SLE (58,(125)(126)(127)(128) .…”
Section: Diet Epigenetic and Sle Linkagementioning
confidence: 99%